Microcrédito en Colombia: un análisis desde su evolución y contribución a la disminución de los indicadores de pobreza durante el periodo 2008-2018 (2019)
The microcredit in Colombia began to originate in the mid-1980s with the objective of providing financial support for people with low income, in order to help alleviate poverty. For this reason, it has become a mechanism. In favor of financial inclusion since it fosters the country's economic growth, and, in the same way, positively influences the well-being, quality of life and income of the population. Based on the above, it can be said that microcredit has become one of the factors that contribute to an improvement in the country's poverty levels because, by granting resources to the most vulnerable population, it would be impacting directly in improving your income. Thus, because as evidenced in the development of this research, the relationship between these variables under study is positive since there is an inverse correlation, that is, one variable would be explained with respect to the other. In a nutshell, as the number of microcredit disbursements increases, it will influence the relative decrease in the indicators of monetary and multidimensional poverty both in rural areas and in the headwaters of the country.